Bioconversion of Lantana camara by vermicomposting with two different earthworm species in monoculture. (January 2020) - Devi, Chaichi; Khwairakpam, Meena
Highlights: Bioconversion of L. camara by vermicomposting is feasible. Nutrient quality was enhanced in the final vermicompost with highest TKN 2.78%. C/N ratio was within 11–14 for all the reactors and highest 32.46% TOC change. E. fetida is more efficient in bioconversion of L. camara. Mixing proportion of 60% was most desired ratio for both the earthworm species. Abstract: The experiments were performed in bamboo containers with five different reactors (Ref 1/Ree 1, Ref 2/Ree 2, Ref 3/Ree 3, Ref 4/Ree 4, Ref 5/Ree 5) of varying substrate and cow dung ratio for earthworms i.e. Eisenia fetida and Eudrilus euginae. Physicochemical properties of the vermicompost produced by each earthworm were evaluated and the performance of both the earthworms was compared. pH was within 7.1–7.5 for all the reactors. The highest Total Kjedahl Nitrogen (TKN) value was found for Ref 4 with 2.78% whereas it was lowest for Ree 1 (2.48%). The highest 32.46% change in Total Organic Carbon (TOC) was observed for Ref 3. At the end of the process C/N ratio was found within 11–14 for both the earthworms. In terms of growth both the earthworms performed well whereas highest net biomass gain for Eisenia fetida in Ref 3 with 37.5%. Vermicomposting is found to be beneficial for the management of Lantana camara . Eisenia fetida performed better as compared to Eudrilus euginae.